Food from the ocean; towards a research agenda for sustainable use of our oceans' natural resources. (July 2019) - van Hoof, Luc; Fabi, Gianna; Johansen, Vegar; Steenbergen, Josien; Irigoien, Xabier; Smith, Sarah; Lisbjerg, Dennis; Kraus, Gerd
Abstract: By 2050 it is expected that food, clean drinking water and sustainable energy has to be produced for a world population of close to 10 billion people. Our seas and oceans represent 71% of earth's surface, yet its space and resources today are not sustainably utilised to their full extent. The importance of the use of the marine environment is within the EU widely acknowledged and reflected in such agendas as the EU Blue Growth strategy, the Food 2030 agenda and the Food from our Oceans vision. In order to substantiate the vision to increasingly feed the world population from our oceans, a foresight exercise was implemented to construct an agenda of the science needed in the realm of fisheries, aquaculture and seafood. This resulted in a research agenda that is logically argued and based on an analysis made by stakeholders and experts which led to the identification of priorities having a scientific analytical basis as well as a societal reference. The process and the results of this foresight exercise are presented and are put in the wider context of Europe's research agenda towards 2050. In order to bring about the required Blue Revolution, substantial effort should be rendered to the science and innovation needed to support this development.